Inclusive sports in Philippine higher education: Determining attitudes towards transgender students’ participation - Mark Gabriel Wagan Aguilar (SIMULACRA: JURNAL SOSIOLOGI, 2023)
With the increasing global awareness and recognition of transgender rights and inclusion in various fields, including sports, it is crucial to examine what sports stakeholders think about the participation of transgender people in sports competitions, especially in the Philippines where there is a lack of studies on the topic. This motivated the researcher to conduct this study. Guided by a descriptive research design and using a quantitative-qualitative research approach, this study aims to determine the attitudes towards the participation of transgender athletes in sports, starting with randomly selected athletes from Philippine Higher Education Institutions (HEIs). Data were collected through a survey and structured interviews, with questions validated by experts. Findings indicate that the future of sports in Philippine colleges is likely to be inclusive, with student-athletes having positive attitudes towards the idea of allowing trans women and trans men to compete in women’s and men’s sports categories, respectively, and towards the creation of separate sports categories for trans individuals only. This study can help higher education institutions develop more inclusive and respectful athletic practices that promote diversity and equal opportunity for all students who wish to participate on athletic teams and represent their colleges or universities, regardless of gender.